Groundwater Recharge and Hydrogeochemical Evolution in Leizhou Peninsula, China - Yintao Lu; Changyuan Tang; Jianyao Chen; Junhong Chen (Journal of Chemistry)
An analysis of the stable isotopes and the major ions in the surface water and groundwater in the Leizhou Peninsula was performed to identify the sources and recharge mechanisms of the groundwater. In this study, 70 water samples were collected from rivers, a lake, and pumping wells. The surface water was considered to have a lower salinity than the groundwater in the region of study. The regression equations for δD and δ18O for the surface water and the groundwater are similar to those for precipitation, indicating meteoric origins. The δD and δ18O levels in the groundwater ranged from −60‰; to −25‰; and −8.6‰; to −2.5‰, respectively, and were lower than the stable isotope levels from the winter and spring precipitation. The groundwater in the southern area was classified as the Ca2+-Mg2+-HCO3--type, whereas the groundwater in the northern area included three types (Na+-Cl−-type, Ca2+-Mg2+-HCO3--type, and Ca2+-Mg2+-Cl−-type), indicating rapid and frequent water-rock exchange in the region. A reasonable conclusion is that the groundwater chemistry is dominated by rock weathering and rainwater of local origin, which are influenced by seawater carried by the Asian monsoon.